2011
DOI: 10.1590/s0034-737x2011000500001
|View full text |Cite
|
Sign up to set email alerts
|

Indução de embriões somáticos a partir de embriões zigóticos de Heliconia bihai (L.) L. cv. Lobster Claw Two

Abstract: Somatic embryogenesis from zygotic embryos of Heloconia bihai (L.) L. cv. Lobster Claw TwoTropical flowers have contributed to the growth of the cut flower market in Brazil, especially plants of the genus Heliconia. Heliconias are usually propagated vegetatively, although this method can spread diseases and in the near future may severely comprise commercial flower production. In vitro cultivation represents an important potential alternative for guaranteeing the production of high-quality heliconia planting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 19 publications
(16 reference statements)
3
4
0
2
Order By: Relevance
“…Similar results were also observed by Pant & Thapa (2012) [13] in orchids and souza (2010) [28] found that the best shoot formation was observed in a combination of BAP and GA 3 . These same results were in conformity with findings of Ulisses (2010) [32] who observed that ½ MS medium promoted best shoot formation in Heliconia. Development of shoots was observed at 45 days after inoculation in Heliconia (Araujo, 2012) [27] .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were also observed by Pant & Thapa (2012) [13] in orchids and souza (2010) [28] found that the best shoot formation was observed in a combination of BAP and GA 3 . These same results were in conformity with findings of Ulisses (2010) [32] who observed that ½ MS medium promoted best shoot formation in Heliconia. Development of shoots was observed at 45 days after inoculation in Heliconia (Araujo, 2012) [27] .…”
Section: Resultssupporting
confidence: 93%
“…The lowest percentage (45%) of results was recorded in the Control (C), T 2 Gibberellic acid (GA 3 ) @ 3 mg L -1 , T 4 GA 3 @ 1mg L -1 + Benzyladenine (BA) @ 1 mg L -1 treatments. The same result was obtained by Ulisses (2010) [32] in Heliconia bihai L. with use of media containing sucrose. Our results showed that a GA 3 and BA significantly improved in vitro germination of embryos from S. reginae.…”
Section: Resultssupporting
confidence: 86%
“…Lobster Claw Two (Ulisses et al, 2011) e em maracujá -Passiflora edulis Sims (Pinto et al, 2012), estando intimamente ligados aos fatores supracitados, bem como às condições de cultivo e ao tipo de explante utilizado.…”
Section: Introductionunclassified
“…Somatic embryogenesis is generally induced by strong auxins i.e. more stable to degradation (ULISSES et al, 2011). In anthurium, 2,4-dichlorophenoxyacetic acid (2,4-D) and naphthaleneacetic acid (NAA) are, in that order, the most commonly used auxins.…”
Section: Introductionmentioning
confidence: 99%
“…De maneira geral, a embriogênese somática é induzida por auxinas fortes, ou seja, mais estáveis à degradação (ULISSES et al, 2011). Em antúrio, o ácido 2,4-diclorofenóxiacético (2,4-D) e o ácido naftalenoacético (ANA) são, nesta ordem, as auxinas mais utilizadas.…”
Section: Introductionunclassified